Application of CeO2-V2O5 catalysts in the oxidative desulfurization of 4, 6-dimethyl dibenzothiophene as a model reaction to remove sulfur from fuels. (September 2022) - Elena Manríquez-Ramírez, Ma.; Valdez, Martín Trejo; Castro, Laura V.; Flores, Miriam Estrada; Ortiz-Islas, Emma
Highlights: V2 O5 and CeO2 catalysts and their mixture were prepared by incipient impregnation method. The V2 O5 /CeO2 catalytic properties were evaluated in the 4, 6-dimethyl dibenzothiophene oxidation. V2 O5 /CeO2 catalysts showed surface acidity increasing with the addition of vanadium oxide. Surface area and surface acidity affected the catalytic activity. The catalyst with the highest amount of vanadium oxide had a conversion rate of nearly 100% . Abstract: Oxidative desulfurization (ODS) is an excellent alternative for removing sulfur from fuels and the accurate choice of catalyst is essential in obtaining good conversion. In this study, V2 O5 and CeO2 catalysts and their mixture were prepared by incipient impregnation method from ammonium metavanadate and cerium chloride as precursors. The catalysts were characterized by different physicochemical techniques. The acidity of the catalyst was measured potentiometrically by titration with pyridine and using a platinum electrode. The catalytic properties of the synthesized catalysts were evaluated in the ODS of 4, 6-dimethyl dibenzothiophene. Acidity increased with the addition of vanadium, which generated more variants in the oxidation state of V2 O5 and improved the catalytic activity. The vanadium catalyst with the highest amount of vanadium oxide achieved a conversion rate of nearly 100%, renders a viable catalyst for sulfur removal. Factors such as acidity and surface area affect the catalytic activity. Graphical abstract: Image, graphical abstract